Root Resorption in Orthodontic Treatment: Scoping Review - Aryal, Neeta; Jing, Mao (Orthodontic Journal of Nepal, 2017)
Introduction: Root resorption is the loss of apical root tissue leading to the shortness of root which is often evident in orthodontic tooth movement. Proper management during orthodontic treatment however can minimize this undesirable outcome. The present article attempts to review the etiology of root resorption, methods of diagnosis, and strategies for prevention. Materials & Method: A scoping review was done with the purpose to carry out the narrative integration of the relevant evidences on root resorption and orthodontic treatment from the published literatures. The resulting papers were studied and reviewed thoroughly for the key explanation of root resorption in orthodontic patients. A total of 41 published research articles were reviewed. Discussion: According to the literatures root resorption is common iatrogenic outcome in orthodontic treatment. Biological, mechanical, and combined biological and mechanical factors result in external root resorption. Though most clinicians diagnose root resorption by conventional radiography, researches have clearly shown that CBCT is the promising tool. The clinicians need to counsel orthodontic patients and their parents that the root resorption might be a potential consequence of the treatment lasting for long time. In case of severity; it is essential to reassess the patient and minimize the underlying cause. It is necessary to understand the role of orthodontist in preventing root resorption